2019
DOI: 10.3390/nu12010088
|View full text |Cite
|
Sign up to set email alerts
|

FOODLIT-PRO: Food Literacy Domains, Influential Factors and Determinants—A Qualitative Study

Abstract: Poor eating habits are increasing the prevalence of weight-related issues, such as diabetes and cardiovascular diseases. Given the demand to improve individuals’ food knowledge and competencies aiming at healthier behaviours, the current investigation explores the concept of food literacy. Considering the lack of a shared understanding of food literacy, this study aims to explore food literacy’s domains, influential factors and determinants. Using a qualitative deductive-dominant content analysis, 30 experts f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 74 publications
1
52
2
2
Order By: Relevance
“…Any type of studies available in English featuring interventions that contain one or more components of food literacy/nutrition literacy [36], including understanding of food and nutrition information, knowledge of food and nutrition, the skill of finding information from various sources, meal and snack preparation, increasing the consumption of fruits and vegetables, reducing the consumption of prepared foods, healthy food choice, and the skill of reading and analyzing food labels in school setting, will be included in the review without considering the time limit. The studies that focus on nutritional interventions related to diseases such as type II diabetes and obesity will be excluded.…”
Section: Types Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any type of studies available in English featuring interventions that contain one or more components of food literacy/nutrition literacy [36], including understanding of food and nutrition information, knowledge of food and nutrition, the skill of finding information from various sources, meal and snack preparation, increasing the consumption of fruits and vegetables, reducing the consumption of prepared foods, healthy food choice, and the skill of reading and analyzing food labels in school setting, will be included in the review without considering the time limit. The studies that focus on nutritional interventions related to diseases such as type II diabetes and obesity will be excluded.…”
Section: Types Of Interventionsmentioning
confidence: 99%
“…If sufficient studies are identified and data points are available, potential sources of heterogeneity will be investigated further by subgroup or meta-regression analysis according to baseline characteristics and methodological covariates. We plan to conduct analyses by sex (girls vs boys) [47], age (e.g., children vs adolescent, midpoint of age range as continuous variable) [36,47], type of study (RCT, casecontrol, pre-post, etc. ), food literacy/nutrition literacy level (e.g., low, moderate or high), sample size (e.g., < 1000, 1000-5000, or > 5000 participants), and study quality (e.g., low/moderate vs high-risk of bias).…”
Section: Additional Analysesmentioning
confidence: 99%
“…Food literacy is desperately needed in university students, including those students preparing for health professions [ 50 ]. From our food literacy survey, more than 75% of the participants in our pilot study, who were mainly nursing and health sciences students, scored below 75%.…”
Section: Discussionmentioning
confidence: 99%
“…We were also able to show an almost 20% increase in sales with meals-to-go, all of which persuaded DHS to start FND. Unfortunately, socio-economic status is often predictive of healthy eating, also in college students [ 50 ], and food insecurity on college campuses is high [ 53 ]. It has to be stated that FND-like dining operations do not have to generate revenue, as their value proposition is expansive and goes beyond simply getting a healthy meal on campus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation